Development and Validation of a VO₂max-Based Standard for Talent Identification in Adolescent Competitive Swimmers - Achmad Widodo; Abdul Aziz Hakim; Irmantara Subagio; Mohammad Noval Baghaskara (INSPIREE: Indonesian Sport Innovation Review, 2026)
The  purpose  of  the study. This study aimed to develop and validate a VO₂max-based eligibility standard to serve as an objective physiological benchmark for talent identification and selection of adolescent competitive swimmers in Age Group 2 (KU 2, ages 13–15 years) within the Indonesian national training system. Materials and methods. A Research and Development (R&D) design was employed, guided by the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Eight elite national swimmers (four male, four female; mean age 14.5 ± 0.5 years) from the National Potential Young Athlete Training Center (SLOMPN) in Cibubur, East Jakarta, were recruited. Two swimming-specific field test protocols were administered: (1) the Aerobic Swim VO₂max Test 15 Minutes (modified Balke protocol) and (2) the Cooper Swimming Test 12 Minutes. Descriptive statistics, protocol comparison, and cut-off score determination were applied to empirical data.. Results. The 15-minute Balke modified protocol demonstrated superior ecological validity in capturing steady-state aerobic capacity relative to the 12-minute Cooper test. Mean VO₂max values for male athletes were 55.25 ± 0.50 mL/kg/min (12-min) and 58.25 ± 0.50 mL/kg/min (15-min), yielding a composite mean of 56.75 mL/kg/min. Female athletes recorded 45.00 ± 0.00 mL/kg/min (12-min) and 47.75 ± 0.50 mL/kg/min (15-min), with a composite mean of 46.38 mL/kg/min. VO₂max eligibility thresholds for the Superior performance category were established at ≥ 56.7 mL/kg/min for males and ≥ 46.3 mL/kg/min for females. Conclusions. The developed VO₂max standards provide a scientifically grounded, sex-specific, and ecologically valid framework for talent identification in adolescent competitive swimmers. Implementation of these thresholds is recommended across national and regional training centers to minimize subjective selection bias and ensure athletes' physiological readiness for high-performance competition. Future research should expand the normative sample and incorporate direct gas analysis cross-validation.